Optimization of β-Carotene-Fortified Chocolate Bar Formulation Based on Sensory Evaluation Using the Taguchi and Zero-One Methods - Sidik, Gusmon; Makosim, Syahril; Sukotjo, Setiarti (Jurnal Ilmu Gizi dan Dietetik, 2026)
Consumer interest in functional food products has driven the need for innovation in chocolate bars through β-carotene fortification, a carotenoid compound that functions as an antioxidant and has the potential to support the prevention of Non-Communicable Diseases (NCDs) such as diabetes. This study aimed to ensure that β-carotene fortification does not reduce the quality of chocolate bars based on sensory evaluation, so that the product remains acceptable to consumers. The research applied an engineering approach using the Taguchi Method, selected for its ability to optimize formulations efficiently with a minimal number of experiments. Four factors were evaluated: cocoa nibs, cocoa butter, β-carotene, and sugar, each at three levels. The Zero-One Method was used to determine the best formulation based on sensory scores and technical constraints, as it enables optimal alternative selection under multi-criteria conditions. The analysis results showed that the formulation with the best sensory quality was Concept 5, with a total score of 22.22%. Concept 5 consisted of treatment A2 (200g cocoa nibs), B2 (235g cocoa butter), C3 (7g β-carotene), and D1 (250g sugar), which produced the most preferred sensory characteristics among consumers, including an attractive chocolate color, a strong cocoa aroma, a well-balanced sweet-bitter taste, a smooth texture that melted easily in the mouth, and an aftertaste that did not leave excessive bitterness. The β-carotene content of the selected formulation reached 91.12 μg/g (equivalent to 0.091 mg/g). Consumption of 30 g of the chocolate bar per day can provide an intake of 2.73 mg of β-carotene, equivalent to 45.5–91.0% of the minimum recommended daily β-carotene intake range for humans. The results demonstrated that the application of the Taguchi Method and Zero-One Method was effective in optimizing the formulation of β-carotene-fortified chocolate bars, resulting in a product with desirable sensory quality and enhanced functional value.